Aging in a Neoclassical Theory of Labor Demand - Thomas Christiaans (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2003)
This paper introduces aging of workers into the neoclassical theory of labor demand. Among other things, it is shown that under reasonable hypotheses employment, even of younger workers, increases in the span of working life. Using the standard model without aging, the analysis of such issues has not been possible up to now. The main results derived for constant returns to scale carry over to the qualitatively equivalent steady state of a model with decreasing returns to scale. Thus, constant returns to scale loose much of their special flavor. The implied age-structure of optimum employment turns out to accord well with empirical evidence.
Keywords: D92; J23; 330; Labor Demand; Aging; Adjustment Costs; Arbeitsnachfrage; Altersgruppe; Skalenertrag; Theorie; Alternde Bevölkerung